Long-term constancy of two rain-call dialects of the Chaffinch Fringilla coelebs in Finnish and Russian Karelia. A consequence of site fidelity? - Sorjonen, J. (BirdLife Finland, 2001)
According to old Finnish ornithological literature, two different rain-call dialects of the Chaffinch existed in eastern Finland at the end of the 19th century and the beginning of the 20th century. In this work I studied the current existence and range of distribution of different rain-call dialect areas in Finnish and Russian Karelia. Raincall vocalization is strongly connected to breeding time and uttered only by males. However, males sang the full song five times as often as they uttered the rain-call in Finland and three times as often as they uttered the rain-call in the Karelian Isthmus. The proportion of rain-call of all vocalizations (song and rain-call) increased from morning towards evening and from spring to the middle of summer. Males that uttered the "hüit" dialect sang the real song relatively more often than males that uttered the "krik" dialect. In the study area of about 60 000 km2, there were only two large dialect areas. The "hüit" dialect occurred in the northwestern part (eastern Finland and the northern part of the Karelian Isthmus) and "kriek" occurred in the southeastern part (central and southern parts of the Karelian Isthmus and on the eastern coast of Lake Ladoga) of the study area . The rain-call dialects were not related to specific habitat types. The two dialects occured both in coniferous and deciduous forests. Between the two dialect areas is a 50 to 180 km wide sympatric zone in which both dialects were found and where every year some males uttered "hybrid" calls and some were also bilingual. The sympatric zone, where both dialects occurred, was biased northwards from the line where both dialects were equally common (50%). The two dialect areas seemed to have remained rather constant for least 120 years. The strong persistence presumably results from the strong site-fidelity of the adult breeders and from the weak dispersal rate of yearlings (+1 year old) .